2020
DOI: 10.1136/ijgc-2019-000860
|View full text |Cite
|
Sign up to set email alerts
|

Cervical versus endometrial injection for sentinel lymph node detection in endometrial cancer: a randomized clinical trial

Abstract: ObjectiveTo evaluate the relationship between pelvic/para-aortic sentinel lymph node status and two different injection sites of 99m-technetium (99mTc)-labeled phytate in patients with endometrial cancer.MethodsThis was a randomized controlled trial involving 81 patients with endometrial cancer. In the cervical group (n=40), injections of 99mTc were performed at the 3 and 9 o’clock positions of the uterine cervix. In the endometrial group (n=41), 99mTc was injected into the fundal endometrium using a transcerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
0
12
0
5
Order By: Relevance
“…However, the potential risk of missing PLN-PAN+ remains one of the main concerns and criticisms ( 30 , 34 ), because SLN labeling on cervical tracer injection may not adequately map the PAN area ( 35 ). Then, additional fundal site injections of SLN labeling are needed to improve the assessment of PANs ( 36 , 37 ). Multinu et al found that ultrastaging and pathologic review can identify occult pelvic lymph node metastases and reduce the prevalence of true PLN-PAN+ ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential risk of missing PLN-PAN+ remains one of the main concerns and criticisms ( 30 , 34 ), because SLN labeling on cervical tracer injection may not adequately map the PAN area ( 35 ). Then, additional fundal site injections of SLN labeling are needed to improve the assessment of PANs ( 36 , 37 ). Multinu et al found that ultrastaging and pathologic review can identify occult pelvic lymph node metastases and reduce the prevalence of true PLN-PAN+ ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations have attempted to develop new methods to improve the detection rate of para‐aortic SLNs such like subserosal myometrial injection of the uterine fundus and hysteroscopy‐guided subendometrial tumor injections 12,13 . The data showcase that comparing with pelvic SLNs, fundus injection could better perceive para‐aortic SLNs 4,14 . Based upon the data, we suggest that fundal injection combined with cervical injection might be more efficient than cervical or fundal injection alone for intermediate‐high‐risk EC patients to detect pelvic and para‐aortic SLNs.…”
Section: Introductionmentioning
confidence: 76%
“…12,13 The data showcase that comparing with pelvic SLNs, fundus injection could better perceive paraaortic SLNs. 4,14 Based upon the data, we suggest that fundal injection combined with cervical injection might be more efficient than cervical or fundal injection alone for intermediate-high-risk EC patients to detect pelvic and para-aortic SLNs.…”
Section: Several Investigations Have Attempted To Develop New Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…The principles of operation detect the presence of gamma radiation, distinguish differences in the amount of gamma radiation emitted from different areas of the body or an organ, and translate the gamma energy pulses received by the detection probe into audible and numerical signals. Administration is performed by the nuclear physician in the sentinel lymph node (Pin, 2017;Gezer et al, 2020).…”
Section: Resultsmentioning
confidence: 99%